The balance between project performance and stakeholders ́ satisfaction in projects with the support of project management offices - Barbalho, Sanderson César Macêdo (2019)
PMOs emerged as entities dedicated to support management in organizations which run large and/or complex projects. PMOs have been used in several companies and have a wide variety of roles. Our recent research shows some relations between PMO functions and project´s performance in new product development (NPD) projects. Nevertheless, deepening our study we found some evidences that show a difficult relation among project´s stakeholders and performance. We run two deep case studies about the relations between project performance and stakeholders´ satisfaction. The first was done in a company that develops new products. The second in a public organization devoted to industryuniversity programs. Our results suggest that even in highly effective project management in terms of performance, stakeholders’ satisfaction is more important than the risk of declining this own organizational performance. Therefore, managers must take a balance between projects´ performance and stakeholder´s satisfaction in form to avoid abrupt changes in project management structure and practice with the risk of declining project successes.